Sri Lanka Jobs Diagnostic - Ruppert Bulmer, Elizabeth (World Bank, Washington, DC, 2020)
This report outlines 5 main policy channels for interventions to help the Sri Lankan economy modernize and move beyond yesterday’s labor-intensive strategies to more skill-intensive employment in competitive firms: reducing barriers to firm growth and productivity, revising labor market, government employment, and competition policies; enhancing youth and women's capacity to obtain better jobs; increasing the productivity of the self-employed; and improving matching of job seekers with employers.